BOOSTING THE HARVESTING OF NIGERIA’S ABUNDANT RENEWABLE ENERGY POTENTIALS AND LEGAL IMPLICATIONS: Received: 02nd May 2022; Revised: 13th June 2022, 28th June 2022; Accepted: 29th June 2022 - Chineke, T C; Ozuomba, J O; Anumaka, M C; Ojiaka, J C; Akwuegbu, O C (MATTER: International Journal of Science and Technology, 2022)
Renewable energy has been highlighted not only as a means of satisfying the energy needs of Nigerians but also as a tool for the country’s growth, thereby improving the income of the citizens who have more energy to work with, serving as the energy source for domestic and office use, in addition to reducing the carbon footprint from the conventional fossil fuels. From data obtained from the Photovoltaic Geographic Information System (PVGIS), the solar electricity potential at some selected cities in Southern Nigeria that ranges from 4.5 to 6.5 kWh/m2 has been presented as a tool, which when properly harnessed, can be used to mitigate avoidable energy-related “national disasters” such as unemployment and youth-restiveness, thereby accelerating Nigeria’s development. There is the urgent need to revise and effectively implement helpful laws and policies that support the addition of renewable energy sources for electricity generation. Lack of a coherent legal framework with incentives for the utilization of renewable energy is among the key factors causing poor utilization of renewable energy in Nigeria. Governmental and stakeholder collaboration is highly necessary for developing countries to robustly track renewable electricity adoption via laws aimed at boosting its adoption.